The effectiveness of using the Cooperative Integrated Reading and Composition model To improve the reading skill in teaching Arabic language for eighth grade students At the Institute of Islamic Education, Tanjung Berulak Kampar/ Fa’aliyah Istikhdami Namujaz Ta’lim Cooperative Integrated Reading and Composition Litarqiyati Maharah al-Qira’ah fi Ta’lim al-Lughah al-Arabiyah lada Thullabi as-Shaffi at-Tsamin fi Ma’had at-Tarbiyah al-Islamiyah Tanjung Berulak Kampar - Jannah, Miftahul; Zulkifli, Zulkifli (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
It was a quasi-experimental research aiming at knowing the effectiveness of using Integrated Reading and Composition learning model in increasing student reading skill at the eighth grade of Islamic Junior High School of PPMTI Tg. Berulak, Kampar. The formulation of the problem was “was the use of Using Integrated Reading and Composition learning model effective in increasing student reading skill at the eighth grade of Islamic Junior High School of PPMTI Tg. Berulak, Kampar?” This research was started by planning the lesson plan, implementing, observing, and testing. The eighth-grade students at Islamic Junior High School of PPMTI Tg. Berulak, Kampar in the Academic Year of 2021/2022 were the population of this research, and the samples were the eighth-grade students of classes A and B. The subjects of this research were the eighth-grade students, and the object was the effectiveness of using Integrated Reading and Composition learning model in increasing student reading skill at the eighth grade of Islamic Junior High School of PPMTI Tg. Berulak, Kampar. Observation and test were the instruments of collecting data. Based on data analysis, it could be concluded that the use of Integrated Reading and Composition learning model was effective in increasing student reading skill at the eighth grade of Islamic Junior High School of PPMTI Tg. Berulak, Kampar because the score of to 3.44 was higher than tt 2.563 at 1% significant level and 2.074 at 5% significant level. It meant that Ha was accepted and H0 was rejected. In other words, Integrated Reading and Composition learning model was effective in increasing student reading skill at the eighth grade of Islamic Junior High School of PPMTI Tg. Berulak, Kampar.